A study of the ionic diffusion under the effect of electric field (computer simulation with reference to biological membrane) - Fawzy, Hagar Mohamed (AUC Knowledge Fountain, 2013)
The biophysical studies of the biological system are far from being conclusive. Not only because this science is relatively recent, but also because of the lack of physical data. Also there are a lot of contradicting views among researchers as well as the poor theoretical interpretation of the reported experimental data. However, the advent of computer science with the considerable storage capability and highly vast calculations gives modeling techniques a great advantage and opens a real door to better understanding of the complicated biological phenomena. The present thesis addressed the problem of ionic penetration through biological tissue under the effect of external electric field (DC and AC). This was done by studying the diffusion coefficient D as an indicating parameter for such effects. The work was based on stochastic computer simulation of the problem such that the tissue was considered as a matrix that contains the elements under study. The size of the matrix was up to 30,000 x 30,000. Two dimensional honey comb cellular pattern was simulated such that it allowed six maximum possible element-to-element communications. The diffusants were let to diffuse under different electric field strengths in DC forward and opposite directions, and AC field with different frequencies. The effect of vacancies concentration and annealing time were tested in the absence of electric field. Two different vacancies concentrations were studied under the effect of electric field. Fist, 90% of the tissue was vacant and subjected to DC and AC fields as well as zero field. Second, 50% of the tissue was vacant and investigated under similar conditions. The results showed that for the 90% case, the penetration increased with increasing of electric field strength. While in the 50% case, the penetration increases with increasing the current until a point at which the diffusion is hindered. The DC results of forward current were compared to that of backward direct current and the results showed that the backward direction hindered diffusion. The effect of alternating current shows that penetration was inversely proportional with the frequency which agrees with literature. Comparisons of the effects of sinusoidal and square waves were illustrated. The square waves showed to have more ionic penetration and diffusion coefficient values than the sinusoidal ones. As the frequency of alternating current is decreased, its effect on diffusion became close to that of direct current. Despite the fact that the results obtained by simulation are in essence virtual and based on arbitrary units, yet the effects were clear and indicative.